2020
DOI: 10.1002/aenm.201903589
|View full text |Cite
|
Sign up to set email alerts
|

A High Energy Density Aqueous Battery Achieved by Dual Dissolution/Deposition Reactions Separated in Acid‐Alkaline Electrolyte

Abstract: Aqueous batteries are facing big challenges in the context of low working voltages and energy density, which are dictated by the narrow electrochemical window of aqueous electrolytes and low specific capacities of traditional intercalation‐type electrodes, even though they usually represent high safety, low cost, and simple maintenance. For the first time, this work demonstrates a record high‐energy‐density (1503 Wh kg−1 calculated from the cathode active material) aqueous battery system that derives from a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
129
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 31 publications
0
129
0
Order By: Relevance
“…This aqueous ZnÀ MnO 2 battery with hybrid electrolyte exhibits a high average voltage of 1.7 V due to the lower redox potential of the Zn anode in the alkaline electrolyte. Similarly, Liu et al reported that the electrochemical window of the ZnÀ MnO 2 battery with the alkaline anolyte and the acidic catholyte was broadened to 3 V owing to the high overpotentials of gas evolution in alkaline/acidic conditions, and this battery can output a high voltage of 2.44 V. [18] And a novel bication electrolyte (1 M Al (CF 3 SO 3 ) 3 + 1 M Zn(CF 3 SO 3 ) 2 ) was employed in aqueous ZnÀ MnO 2 batteries to adjust the intermediate species upon charging/discharging, which is intensively associated with voltage, and fianally a high discharge voltage of 1.7 V was obtained due to the formation of the unique Al x MnO 2 species, accompanied with the expansion of the operation voltage window from 1.5 to 1.9 V owing to the suppression of gas evolution by the Al(CF 3 SO 3 ) 3 component. [19] In order to improve the reaction kinetics and structural stability of MnO 2 cathode, clever designs of composite structure are proposed with the aim to provide highly conductive network, more active sites for charge storage, void space to accommodate the volumetric change and/or self-adhesive configuration forming a free-standing electrode.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 95%
“…This aqueous ZnÀ MnO 2 battery with hybrid electrolyte exhibits a high average voltage of 1.7 V due to the lower redox potential of the Zn anode in the alkaline electrolyte. Similarly, Liu et al reported that the electrochemical window of the ZnÀ MnO 2 battery with the alkaline anolyte and the acidic catholyte was broadened to 3 V owing to the high overpotentials of gas evolution in alkaline/acidic conditions, and this battery can output a high voltage of 2.44 V. [18] And a novel bication electrolyte (1 M Al (CF 3 SO 3 ) 3 + 1 M Zn(CF 3 SO 3 ) 2 ) was employed in aqueous ZnÀ MnO 2 batteries to adjust the intermediate species upon charging/discharging, which is intensively associated with voltage, and fianally a high discharge voltage of 1.7 V was obtained due to the formation of the unique Al x MnO 2 species, accompanied with the expansion of the operation voltage window from 1.5 to 1.9 V owing to the suppression of gas evolution by the Al(CF 3 SO 3 ) 3 component. [19] In order to improve the reaction kinetics and structural stability of MnO 2 cathode, clever designs of composite structure are proposed with the aim to provide highly conductive network, more active sites for charge storage, void space to accommodate the volumetric change and/or self-adhesive configuration forming a free-standing electrode.…”
Section: Advances In Science and Technology To Meet Challengesmentioning
confidence: 95%
“…The assembled battery possesses an average discharge voltage plateau of 1.7 V and energy density of 487 Wh kg −1 [92]. In addition, by combining the two dissolution/deposition electrode redox reactions of MnO 2 /Mn 2+ and Zn/Zn(OH) 4 2− using acid-alkaline dual electrolytes and an ion-selective membrane, a high-energy Zn-MnO 2 battery was constructed [93]. The working mechanism is illustrated in Fig.…”
Section: Aqueous Zn-ion Batteries (Azibs)mentioning
confidence: 99%
“…b The principle diagram and the mech-anism of the Zn-MnO 2 battery using the acid-base dual electrolyte under charge and discharge conditions. [93] Reproduced with permission from Ref. [93].…”
Section: Aqueous Zn-ion Batteries (Azibs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Zhou and Liang et al [31] further proposed a dissolution/deposition mechanism for the Zn 2 + storage ability of MnO 2 in mild electrolytes, which believe that dissolution/deposition reactions are the major attributor to the capacity. The discharge side product ZnSO 4 [58][59][60][61] However, a low pH volume will remarkably accelerate the corrosion of Zn anodes and deteriorate the cycling stability of ZIBs. [21] Commonly, the pH of mild ZIBs' electrolytes is higher than 3.…”
Section: Charge Storage Mechanisms Of Mnomentioning
confidence: 99%